1986
DOI: 10.1161/01.str.17.6.1193
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between somatosensory evoked potentials and neuronal ischemic changes following middle cerebral artery occlusion.

Abstract: SUMMARYIn an attempt to determine the usefulness of evoked potentials as a measure of focal cerebral ischemia, we examined somatosensory evoked potentials (SEP's) and morphological neuronal changes in cats following unilateral middle cerebral artery (MCA) occlusion. Fifteen adult cats underwent transorbital occlusion of the MCA under halothane anesthesia. In seven cats the ipsilateral SEP's were abolished after middle cerebral artery occlusion, and did not show any recovery after 6 hours. The same seven cats s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 32 publications
(23 reference statements)
1
9
0
Order By: Relevance
“…First, we killed our cats 6 hours after MCA clipping; therefore, we cannot draw any conclusions about functional impairment or ultimate histologic changes. However, studies by both one of us 17 and by others 22 have shown that distinct histopathologic changes of severe ischemic neuronal damage are evident by 6 hours after MCA occlusion in cats. We also cannot draw any conclusions about the effects of hyperglycemia on noncortical brain tissue since this was not examined.…”
Section: Relation Of Area Of Severe Ischemic Neuronal Damage (Sind) (mentioning
confidence: 94%
“…First, we killed our cats 6 hours after MCA clipping; therefore, we cannot draw any conclusions about functional impairment or ultimate histologic changes. However, studies by both one of us 17 and by others 22 have shown that distinct histopathologic changes of severe ischemic neuronal damage are evident by 6 hours after MCA occlusion in cats. We also cannot draw any conclusions about the effects of hyperglycemia on noncortical brain tissue since this was not examined.…”
Section: Relation Of Area Of Severe Ischemic Neuronal Damage (Sind) (mentioning
confidence: 94%
“…19 SEP amplitudes were then expressed as a percentage of the initial (pretreatment) amplitude for purposes of statistical analysis. Latencies of the major positive and major negative deflections were determined.…”
Section: Methodsmentioning
confidence: 99%
“…After MRI, the brains were prepared for histopathology as described. 16 21 was assessed in the left neocortex and striatum. These microscopic observations were delineated on an enlarged transparency of the slide.…”
Section: -18mentioning
confidence: 99%